Melatonin supplementation can ameliorate the detrimental effects of heat stress on performance and carcass traits of Japanese quail - Şahin, Nurhan; Onderci, M; Şahin, Kazım; Smith, MO (Springernature, 2003)
Melatonin, the major pineal hormone, modulates growth in poultry by influencing hormones involved in growth. We investigated the effects of dietary melatonin supplementation on performance, carcass characteristics, and excretion of nitrogen and some minerals in broiler Japanese quails (Coturnix coturnix japonica) exposed to high-ambient-temperature stress (34degreesC). One hundred twenty Japanese quails (10 d old) were randomly assigned to 4 treatment groups, 3 replicates of 10 birds each. The birds were kept in either an environment-controlled room at a constant 22degreesC or were kept at 22degreesC for 16 h/d and at 34degreesC for 8 h/d (9:00 AM to 5:00 Pm). At both temperatures birds were fed either a basal diet or the basal diet supplemented with 40 mg of melatonin per kilogram of diet. The experiment lasted for 32 d. Melatonin improved feed efficiency in both temperatures groups compared with their corresponding controls. Although feed intake was similar in all groups, the improvement in feed efficiency was more noticable in melatonin-fed quails kept at high temperature (p < 0.01). Supplemental melatonin significantly increased live weight gain and carcass characteristics under stress conditions (p < 0.01) but did not show the same effect at thermoneutral conditions (p > 0.05). Heat exposure increased excretion of N, Ca, P, Zn, Fe, and Cr and decreased retention rates for them. Dietary melatonin supplementation returned these values to normal (p < 0.01). No interactions between melatonin and temperature were found in the parameters measured. The results of the study show that melatonin supplementation attenuated the retardation in performance as well as the excretion of minerals caused by heat stress in broiler quails. Our data suggest that melatonin might offer protection against heat-stress-related depression in the performance of broiler quails.
Keywords: heat stress; quails; melatonin; performance; mineral